2012
DOI: 10.1590/s1517-83822012000300043
|View full text |Cite
|
Sign up to set email alerts
|

Increase of stress resistance in Lactococcus lactis via a novel food-grade vector expressing a shsp gene from Streptococcus thermophilus

Abstract: The effects of the expression of a small heat shock protein (shsp) gene from Streptococcus thermophilus on stress resistance in Lactococcus lactis under different environmental stresses were investigated in this study.pMG36e-shsp, an expression vector, was first constructed by inserting a shsp open reading frame (ORF) cloned from S. thermophilus strain St-QC into pMG36e. Then, a food-grade expression vector, pMG-shsp, was generated by deleting the erythromycin resistance gene from pMG36e-shsp. The transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…). It has been shown many times that both heterologous and homologous overexpression of sHsp confers increased tolerance to heat or salt stress, indicating that although a sHsp has evolved its role under specific circumstances it still contributes to protein protection in general (Salas‐Muñoz et al ., ; Tian et al ., ; Kim et al ., ; Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…). It has been shown many times that both heterologous and homologous overexpression of sHsp confers increased tolerance to heat or salt stress, indicating that although a sHsp has evolved its role under specific circumstances it still contributes to protein protection in general (Salas‐Muñoz et al ., ; Tian et al ., ; Kim et al ., ; Wang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The betaine uptake system from Listeria monocytogenes was introduced into Bifidobacterium breve to increase resistance to gastric acid (Sheehan et al 2007). The acid tolerance of L. lactis was enhanced by overexpressing molecular chaperone proteins DnaK (Tian et al 2012) as well as the DNA repair protein RecO (Wu et al 2013). Table 2 lists the genes involving in acid tolerance of microbes which have been verified through genetic manipulation.…”
Section: Enhancement Of Organic Acid Production By Acid-tolerant Strainsmentioning
confidence: 99%
“…Because L. lactis itself does not contain Hsp genes, expression of the small heat shock protein Lo18 from O. oeni improved the tolerance of L. lactis to heat and acid conditions [16] . Then, the small heat shock protein gene from Streptococcus thermophilus was expressed in L. lactis ML23, and the results showed that the expression of Hsps inserted in the food-grade vector pMG made L. lactis ML23 resistant to environmental stress [17] . It is resistant to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%